Connecting Euler and Lagrange systems as nonlocally related systems of dynamical nonlinear elasticity - Bluman, G.; Ganghoffer, J.F. (Archives of Mechanics, 2011)
Nonlocally related systems for the Euler and Lagrange systems of two-dimensional dynamical nonlinear elasticity are constructed. Using the continuity equation, i.e., conservation of mass of the Euler system to represent the density and Eulerian velocity components as the curl of a potential vector, one obtains the Euler potential system that is nonlocally related to the Euler system. It is shown that the Euler potential system also serves as a potential system of the Lagrange system. As a consequence, a direct connection is established between the Euler and Lagrange systems within a tree of nonlocally related systems. This extends the known situation for one-dimensional dynamical nonlinear elasticity to two spatial dimensions.